KETERLIBATAN MASYARAKAT DALAM MENCAPAI TUJUAN PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - Rahmawati, Diya Rofika; Yuliyanto, Riyan (Universitas Tanjungpura, 2023)
This study aims to determine the implementation of the implementation of the concept of School-Based Management (SBM) at SMKN 1 Surakarta in achieving educational goals. The research method used is to use descriptive qualitative based on primary data in the form of observations and interviews as well as secondary data sourced from journals, documentation, and other relevant sources. The results showed that collaboration between various parties, both internal and external through the involvement of various educational programs proved to be able to assist schools in achieving the goals of providing education and placing SMKN 1 Surakarta with the title of